Immunity and AAV-Mediated Gene Therapy for Muscular Dystrophies in Large Animal Models and Human Trials - Wang, Zejing; Tapscott, Stephen J.; Chamberlain, Jeffrey S.; Storb, Rainer (Frontiers in Microbiology, 2011)
Adeno-associated viral (AAV) vector-mediated gene replacement for the treatment of muscular dystrophy represents a promising therapeutic strategy in modern medicine. One major obstacle in using AAV vectors for in vivo gene delivery is the development of host immune responses to the viral capsid protein and transgene products as evidenced in animal models and human trials for a range of genetic diseases. Here, we review immunity against AAV vector and transgene in the context of gene delivery specific to muscles for treating muscular dystrophies and non-muscle diseases in large animal models and human trials, factors that influence the intensity of the immune responses, and immune modulatory strategies to prevent unwanted immune responses and induce tolerance to the vector and therapeutic gene for a successful gene therapy.